PENINGKATAN KEPUASAN PELANGGAN MELALUI KUALITAS PRODUK, HARGA DAN BRAND IMAGE (STUDI DI THROOX ORIGINAL SURAKARTA) - Faisal Ashari (STIE AUB Surakarta, 2018)
The purpose of this research is to know the influence of product quality, price and Brand Image towards customers satisfaction in Throox Original. The sample of this research as much as 100 respondents. Data analysis tools: test instruments, test the assumptions of classical, linear regression analysis of multiple test, t test, F test, and R2. The results of the regression analysis showed that the quality of the product, the price and the Brand Image of a positive effect towards customer satisfaction. Test results showed that t: product quality, price and Brand Image of a positive and significant effect against customer satisfaction. F test results showed together – the same variable product quality, price and Brand Image effect significantly to customer satisfaction. Test results the coefficient of Determination (R2) of the Adjusted R Square value obtained as a result of 0.667 which means customer satisfaction in Surakarta Throox Original able to be explained by the variable quality of the product, the price and Brand Image of 66,7%, while the remaining 33,3% is explained by other variables did not enter terobservasi. For example: promotion, distribution and quality of service.Keywords: quality of product, pricing, Brand Image and customer satisfaction.